Incels, autism, and hopelessness: affective incorporation of online interaction as a challenge for phenomenological psychopathology - Tirkkonen, Sanna K.; Vespermann, Daniel (Frontiers in Psychology, 2023)
In this article, we analyze self-reported autism in the online communities of involuntary celibates (incels). Instead of focusing merely on the individual experience of autism in the incel community, we investigate how the online environments exacerbate specific vulnerabilities and aggravate hopelessness. Hence, the article combines empirical studies on the incel community with phenomenological and embodiment approaches to autism, hopelessness, and online affectivity. We show how the collective deprivation of hope in the incel forums exceeds the boundaries of these online environments and shapes overall social attunement tendencies online and offline. By investigating characteristic features of incel communities and their potential influence on affective dispositions, our approach contributes to the debate on the current challenges to "situate" phenomenological psychopathology.